Interoperability Governance: An Analysis of the Impact of Digitization of Public Services on Local Government - Dyah Mutiarin; Herman Lawelai; Anwar Sadat; Nastia; Andi Arya Maulana Wijaya; L.M. Azhar Sa'ban (Journal of Local Government Issues, 2024)
The study highlights the significance of understanding the impact of digitalization on public services in local government organizations, particularly about coordination strategy and digitalization policy. The rapid advancements in information technology have transformed the delivery and acquisition of public services, necessitating a comprehensive understanding of the factors influencing the efficiency of digital services.  A quantitative approach was used, with Smart-PLS 3.0 analysis involving respondents from South Buton Regency local government organizations. Data collection was conducted through a direct survey in the field. The results showed a strong relationship between coordination, strategy, and digitalization policy, with a significant relationship between these factors and the effectiveness of digital services. However, no significant relationship between digitalization policy and digital service effectiveness was found. The results of this study provide valuable insights into the dynamics of interoperability governance and the nuanced relationships between coordination, strategy, digitization policy, and digital service effectiveness in local government organizations. Despite the significant influence of coordination and strategy, the role of digitalization policy on digital service effectiveness suggests the need for further evaluation or a change in policy approach. Limitations of this study include the small sample size and focus on one geographical area, so caution is needed in generalizing the findings. Nevertheless, this study contributes significantly to understanding the implementation of digitization in public services, with practical implications for policy development and management practices.